Digital E-Library Model for School Literacy Movement in Elementary Education: Model E-Library Digital dalam Gerakan Literasi Sekolah di Sekolah Dasar - Titik Yuniarti; Muhamad Sofian Hadi; Ahmad Susanto (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Low reading interest and literacy skills among elementary school students in Indonesia remain a persistent educational concern, particularly in relation to limited access to varied and engaging reading resources. Specific Background: Conventional school libraries are constrained by collection diversity, space, and access, while students increasingly interact with digital environments for information and learning activities. Knowledge Gap: Previous literacy initiatives have largely emphasized pedagogical strategies or visual learning media, with limited attention to digital e-library integration as an operational literacy ecosystem within the School Literacy Movement. Aims: This study aims to develop a digital e-library–based School Literacy Movement model and examine its application for fostering reading interest and literacy skills among elementary school students. Results: Using a Research and Development approach with the ADDIE model, the developed digital e-library met criteria of validity, practicality, and feasibility based on expert validation and user responses, alongside observable growth in student reading engagement and literacy performance between pretest and posttest stages. Novelty: The study positions the digital e-library not merely as a reading medium but as an adaptive literacy ecosystem aligned with elementary learners’ digital characteristics. Implications: The findings support the integration of digital e-library models within school literacy programs as a strategic response to conventional library limitations and as a foundation for strengthening literacy culture in elementary education. Highlights • Digital e-library developed as an operational model within the School Literacy Movement• Validation results confirm feasibility and practical classroom application• Literacy activities supported through adaptive digital access to reading materials Keywords School Literacy Movement; Digital E-Library; Reading Interest; Literacy Skills; Elementary Education